Resting Heart Rate Variability Is Associated With Subsequent Orthostatic Hypotension: Comparison Between Healthy Older People and Patients With Rapid Eye Movement Sleep Behavior Disorder - Sumi, Yukiyoshi; Nakayama, Chikao; Kadotani, Hiroshi; Matsuo, Masahiro; Ozeki, Yuji; Kinoshita, Takafumi; Goto, Yuki; Kano, Manabu; Yamakawa, Toshitaka; Hasegawa-Ohira, Masako; Ogawa, Keiko; Fujiwara, Koichi (Frontiers in Neurology, 2020)
Background Orthostatic hypotension (OH) caused by autonomic dysfunction is a common symptom in older people and patients with idiopathic rapid eye movement sleep behavior disorder (iRBD). The orthostatic challenge test is a standard autonomic function test that measures a decrease of blood pressure during a postural change from supine to standing positions. Although previous studies have reported that changes in heart rate variability (HRV) are associated with autonomic dysfunction, no study has investigated the relationship between HRV before standing and the occurrence of OH in the orthostatic challenge test. This study aims to examine the connection between HRV in the supine position and the occurrence of OH in the orthostatic challenge test. Methods We measured electrocardiogram of patients with iRBD and healthy older people during the orthostatic challenge test, in which the supine and standing positions were held for 15 minutes, respectively. The subjects were divided into three groups: healthy controls (HC), OH-negative iRBD (OH (-) iRBD), and OH-positive iRBD (OH (+) iRBD). HRV measured in the supine position during the test were calculated by time-domain analysis and Poincaré plots to evaluate the autonomic dysfunction. Results Forty-two HC, twelve OH (-) iRBD, and nine OH (+) iRBD subjects were included. HRV indices in the OH (-) and the OH (+) iRBD groups were significantly smaller than those in the HC group. The multivariate logistic regression analysis for OH identification for iRBD groups showed the model whose inputs were the HRV indices, i.e., standard deviation 2 (SD2) and the percentage of adjacent intervals that varied by more than 50 ms (pNN50), had receiver operating characteristic curve with area under the curve of 0.840, the sensitivity to OH (+) of 1.000, and the specificity to OH (-) of 0.583 (p = 0.023). Conclusions This study showed the possibility that short-term HRV indices in the supine position would predict subsequent OH in iRBD patients. Our results are of clinical importance in terms of showing the possibility that OH can be predicted using only HRV in the supine position without an orthostatic challenge test, which would improve efficiency and safety of the testing.